Optimisation of intramuscular dosage of dexmedetomidine for hypotensive anesthesia in functional endoscopic sinus surgery- a prospective randomized double blind study - Swarnalingam Thangavelu; Arivumani T A; Elango Dhanapal; Hemlata Kataiyar (International Journal of Medical Research and Review, 2016)
Background of the study: Dexmedetomidine, a selective alpha-2 agonist which is being used widely in anesthesia and critical care practice. It has both sedative and analgesic property. The studies on intravenous usage of dexmedetomidine are numerous but not with intramuscular route. With this background we conducted a study on optimisation of intramuscular dosage of dexmedetomidine in patients undergoing functional endoscopic sinus surgery.Aim and objectives:To optimize the dosage of intramuscular dexmedetomidine in patients undergoing functional endoscopic sinus surgery for providing bloodless field for the surgeon.Materials and methods: We enrolled a total of 50 patients who have planned to undergo functional endoscopic sinus surgery under general anesthesia. After randomization, group D1 patients received intramuscular dexmedetomidine at the dosage of 0.5mcg/kg and group D2 1mcg/kg respectively. Hemodynamic parameters like blood pressure (MAP) and heart rate were recorded at regular intervals. The surgical field score was done by the operating ENT surgeon using Boerzaart scale. The targeted mean arterial blood pressure was kept between 55-65mmHg. The other parameters like additional requirement of opioid, usage of other vasodilators, time to emergence along with other side effects were noted peri-operatively.Results:After statistical analysis, the mean duration of surgery in both groups were 92±21.8 and 85±22.15 minutes respectively. The targeted mean arterial blood pressure was achieved in the patients who have received 1mcg/kg of dexmedetomidine (Group D2) intramuscularly. The surgeon felt satisfied with bloodless operating field in the patients who received 1mcg/kg of dexmedetomidine.Conclusion:From our study we concluded that 1mcg/kg of dexmedetomidine will be the adequate intramuscular dose for both premedication and hypotensive agent in functional endoscopic sinus surgery.